COMPARATIVE ANALYSIS OF TRAINING METHODOLOGY EFFICIENCY ON THE MOTOR SPHERE OF JUNIOR I DANCERS - Grigore Virgil; Grimalschi Teodor (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The purpose of this paper is to highlight the influence of the training methodology on the motor sphere of junior I dancers. This scientific approach has involved the organization of an experimental study in "Two Step" Club of Bucharest. The research activity was conducted from January 2012 to November 2013, by investigating two groups of athletes, an experimental group and a control group; each group included 12 dancers, aged from 12 to 13, corresponding to sports classification category Junior I. The results of the research show that thanks to the training methodology applied to the Junior I dancers included in the experimental group, these ones improved their strength of abdominal and arms muscles, they had an increase of the spine and coxo-femoral joint mobility and they improved their strength under speed conditions as well.